Produksi Enzim Protease Dari A.niger PAM18A dengan Variasi pH dan Waktu Inkubasi - Putri Ramadhani; MG. Isworo Rukmi; Sri pujiyanto (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Advances in the field of fermentation technology, genetic engineering, and technology applications of enzymes lead to the use of enzymes in the industry is increasing. Enzymes used in the industry can be derived from microorganisms such as bacteria, molds, and yeasts. Protease is one of the important enzyme that has been used widely in various fields of industrial application and 65% of the sales of enzymes in the world. Alkaline protease is one of hydrolytic enzymes that can hydrolysis proteins which working at the pH range of 7-12. The aim of this study was to investigate the influence of pH and incubation time on the protease production of A. niger PAM 18A. The experimental were done using Factor Block Random Design with 2 i.e pH of7, 8, 9, and incubation time of 5, 6, 7 days. The results showed that highest protease fromA. niger PAM18A were found in the treatment of pH 8 and of 5 days incubating with the protease activity and specific activity were 0,930 U/mL and 3,632U/mg respectively.Keywords: Production Enzyme, Protease, A. niger PAM18A, pH, incubation time.